The first record of Brandt’s bat Myotis brandtii in the Chernivtsi Region, Ukraine - Mykhailo Drebet (Праці Теріологічної школи, 2016)
Brandt’s bat Myotis brandtii belongs to the group of sibling species of “whiskered” bats. It is one of the least studied bat species of Ukraine. The geographical range of Brandt’s bat covers all administrative regions (provinces) and main natural regions of western Ukraine, except Polissia and Bukovina. In October 2016, in the basin of the Middle Dniester River Valley, near Pryhorodok village, Khotyn district a mummified specimen of Brandt’s bat was found. This finding is the species’ first record in the Chernivtsi region of western Ukraine. In spite of a number of reported records, the range of Brandt’s bat in western Ukraine remains unclear.